Paleoenvironmental investigation of the northern flank of the Olga Basin (Barents Sea) during the Late Weichselian deglaciation - Patel, Jay (UiT Norges arktiske universitet, 2018)
Three gravity cores were collected from an unexplored site in the northern flank of the Olga Basin, Barents Sea. The lack of data from the central Barents Sea prompted this investigation and led to defining the evolution of the environment and ice sheet transitions over the Holocene. The three cores underwent benthic foraminiferal studies in combination with stable isotope analysis of (δ18O and δ 13C) Neogloboquadrina pachyderma, organic compounds and, element geochemistry of sediments and AMS radiocarbon dating of two samples. Two units were identified, Unit 1 found in the upper section of the cores acquired an AMS dating of 9730 ±40 before present (BP) at its base and is recognised as Holocene sediments. Unit 2 is found in the lower section of the cores and is linked to the Late Weichselian. Most of this unit is barren, containing no foraminifera, and along with the presence of ice rafted debris (IRD) it was interpreted as having permanent ice cover and low oxygen due to pyrite minerals found in the sediment. Low Ca/Ti ratio and rising water content marked a transition phase from permanent ice cover in the Late Weichselian to seasonal ice cover in the Holocene. This resulted in finer terrigenous material with higher organic matter content being deposited in Unit 1. The high biological productivity in Unit 1 can be associated with the Atlantic and Arctic waters.